Pengetahuan Dan Persepsi Petani Terhadap Pemanfaatan Pupuk Organik Cair (Bio-Urine Sapi) pada Tanaman Sawi Putih di Desa Netpala Kecamatan Mollo Utara Kabupaten Timor Tengah Selatan - Yuliana Manu; Selfius Nainiti; Kuji Herewila (Undana Press, 2019)
This research was conducted at Netpala Village, North Mollo Subdistrict, Central Middle Timor Regency on September to October 2018. This study aims to determine the characteristics of Cabbage farming using liquid organic fertilizer, knowing the knowledge and perceptions of farmers on the utilization of liquid organic fertilizer at Netpala Village North Mollo Sub-district, South Central Timor Regency. The research was conducted by survey and observation methods, where primary data collection were carried out by direct interviews with respondent farmers which guided by the questionnaire. Secondary data were obtained from relevant institutions or agencies and literature studies. To answer the first goal regarding the characteristics of cabbage farming using liquid organic fertilizer used qualitative descriptive analysis. To answer the second and third objectives to find out the knowledge and perceptions of farmers toward the utilization of liquid organic fertilizer (bio urine) on cabbage plants at Netpala Village which was calculate the percentage value of achieving maximum scores from the average score then compare the percentage score of maximum score with the reference category. At the category where the percentage value be on, that was the category of farmers' knowledge and perceptions toward the utilization of liquid organic fertilizer (cattle bio urine) on cabbage plants at Netapala Village. The results of the study revealed that 80% of respondents belong to productive adult age and 30% to non productive age (>55) years old. Formal education is classified as low (39%) of the total respondens, which is only education up to Elementary Scholol, non formal education (63%), the land area of the respondens is 0,5-1 Ha which is 91%, the highest dependets of respondensts at 4-6 people at 44%, and the highest experience of farming was at >15 years old at 63%. Farmers’ knowledge of the utilization of liquid organik fertilizer (Bio-urine cow) in white mustard plants is in the “Verry High” category with an average score of 55,556%. The level of famers perceptions of the use of organic fertilizer (Bio-urine cow) in chicory plants in Netpala village is in the “Good” category with an average score of 88,89%.s Penelitian ini telah dilakukan di Desa Netpala, Kecamatan Mollo Utara, Kabupaten Timor Tengah Selatan pada bulan September sampai Oktober 2018. Penelitian ini bertujuan untuk mengetahui 1). karakteristik petani sawi putih yang menggunakan pupuk organik cair, 2).mengetahui pengetahuan dan persepsi petani terhadap pemanfaatan pupuk organik cair di Desa Netpala Kecamatan Mollo Utara Kabupaten Timor Tengah Selatan, penelitian dilakukan dengan metode survei dan pengamatan, dimana pengumpulan data primer dilakukan dengan wawancara langsung bersama para petani responden yang berpedoman pada daftar pertanyaan. Data sekunder diperoleh dari lembaga atau instansi terkait serta studi pustaka. Untuk menjawab tujuan pertama mengenai karakteristik responden sawi putih yang menggunakan Pupuk organik cair digunakan analisis deskriptif Kualitatif. Untuk menjawab tujuan kedua mengetahui pengetahuan dan Persepsi Petani terhadap Pemanfaatan pupuk organik cair (Bio-urine sapi) pada tanaman sawi putih Di Desa Netpala yaitu menghitung nilai persentasi pencapaian skor maksimum dari skor rata-rata kemudian membandingkan nilai persentasi pencapaian skor maksimum dengan kategori rujukan. Pada kategori mana nilai presentasi itu berada, itulah kategori pengetahuan dan persepsi petani terhadap pemanfaatan Pupuk organik cair (bio-urine sapi) pada tanaman sawi putih di Desa Netpala. Hasil penelitian diketahui bahwa 80% responden tergolong pada usia dewasa produktif dan 30% usia non produktif (>55) tahun. Pendidikan formal tergolong rendah (39%) dari total responden yakni hanya mengikuti pendidikan hingga tamat SD, pendidikan non formal (63%), luas lahan garapan responden berada pada 0,5-1 Ha yakni 91%, jumlah tanggungan keluaraga responden yang paling tinggi berada pada 4-6 jiwa yakni 44%, dan pengalaman berusahatani responden paling tinggi berada pada >15 tahun yakni 63%. Pengetahuan petani terhadap pemanfaatan pupuk organik cair (Bio-Urine Sapi) pada tanaman sawi putih berada pada kategori “Sangat Tinggi” dengan skor rata-rata 55,56%. Tingkat persepsi petani terhadap pemanfaatan pupuk organik caor (Bio-Urine Sapi) pada tanaman sawi putih di Desa Netpala berada pada kategori “Baik” dengan skor rata-rata 88,89%.